2010
DOI: 10.5016/1980-6574.2010v16n3p658
|View full text |Cite
|
Sign up to set email alerts
|

Efeito relativo da idade em atletas brasileiros de futsal de alto nível

Abstract: IntroduçãoO futsal é um esporte muito praticado no Brasil, e em diversos países do mundo. Estima-se que mais de dez milhões de pessoas praticam esta modalidade ao redor do globo (DACOSTA, 2005). Dentro do contexto escolar, o futsal é ainda mais forte, sendo um dos esportes mais praticados por meninos e meninas (GENEROSI et al., 2008;QUEIROGA et al. 2005). Araújo et al. (1996) descreve que em um jogo de futsal, os esforços são provenientes predominantemente da velocidade agilidade e potência muscular, sendo ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 10 publications
4
16
0
3
Order By: Relevance
“…As for women futsal, we aimed to investigate, for the first time, the occurrence of this phenomenon. The hypothesis of this study were that men scenario remains the same of four years before 12 , with the possibility of small, and not significant, changes on distribution of players by quarters or semesters, especially because the high amount of men futsal players in Brazil, and the current pedagogical procedures observed on futsal stakeholders to select, and offer oportunities for young players to train and compete. For women, is that do not exist RAE, based on assumptions of other studies on football, which suggests that RAE is more susceptible in sports with a high number of practitioners, what is not the case of Brazilian women futsal.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…As for women futsal, we aimed to investigate, for the first time, the occurrence of this phenomenon. The hypothesis of this study were that men scenario remains the same of four years before 12 , with the possibility of small, and not significant, changes on distribution of players by quarters or semesters, especially because the high amount of men futsal players in Brazil, and the current pedagogical procedures observed on futsal stakeholders to select, and offer oportunities for young players to train and compete. For women, is that do not exist RAE, based on assumptions of other studies on football, which suggests that RAE is more susceptible in sports with a high number of practitioners, what is not the case of Brazilian women futsal.…”
Section: Introductionmentioning
confidence: 93%
“…Brazilian men elite futsal seems to be susceptible to the prevalence of RAE. Penna and Moraes 12 have assessed 370 men athletes, from twenty clubs participating in the 2009 Brazilian Men National Futsal League, and have found significant differences between the first two quarters of the year, always having a greater number of representatives, when compared to those born in the later quarters (1st-29.46%, 2nd-31.62%, 3rd-19.46% and 4th-19.46%). However, the literature on RAE for women's sports is relatively sparse, and no such studies were found on futsal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ainda com relação ao Efeito da Idade Relativa, sabe-se que aqueles atletas favorecidos por essa variável são apontados como mais talentosos e significativamente mais selecionados pelos treinadores para as equipes de futebol 3,5,6 . Observa-se, também, a influência do Efeito da Idade Relativa em outras modalidades 12,13 . Esses atletas favorecidos também são mais convocados para os jogos e participam por mais tempo das partidas do que seus pares nascidos posteriormente 4 .…”
Section: Introductionunclassified
“…It seems that the anthropometrical profile of futsal players is a very important factor for the coaches to organize and evaluate their training process which should be adapted to players' needs (Giusti et al, 2012). Relative age effect is a problem observed at younger ages because of which the majority of players engaged in futsal are those who born the first quartiles of the year of birth because they frequently respond better in anthropometrical and physiological needs than others (Penna, Da Costa, Ferreira, & De Albuquerque Moraes, 2011;Penna & Moraes, 2010).…”
Section: Anthropometrical Characteristics Of Futsal Playersmentioning
confidence: 99%